Postqualitative inquiries into digital study practices in higher education: Interplays of hesitations and speculations. - Hilli, Charlotta (Tidsskriftet Læring og Medier (LOM), 2026)
Research on higher education students’ digital study practices and generative artificial intelligence (GAI) is contradictory. GAI may positively influence students’ learning by providing tailored and diverse feedback. However, if students use GAI unethically or uncritically, it may hamper their deep learning, cognitive and meta-cognitive growth, and problem-solving skills. Few studies provide practical insights into student and GAI collaboration, something this paper addresses. The study employs a postqualitative approach called thinking with theory, situating the researcher, contextual matters, and theories (Bildung, sociomaterialism) as active research participants when analysing student prompts to ChatGPT or Co-pilot in two PowerPoint presentations created by ten students during a bachelor course at Åbo Akademi University. The implications are that GAI created hesitant and speculative interplays that must be addressed to support digital study practices. Furthermore, lively interplays of humans, contextual (e.g., assessment methods) and other matters (e.g., course literature, PowerPoint) can aid in creating epistemic, ethical and aesthetically meaningful study practices in higher education.